DIAGNOSIS OF CHANGES IN THE HEMODYNAMICS OF THE UTERUS AND PLACENTA WITH INTRAUTERINE INFECTION - Rakhimova Kamola Yuldashevna (Scholar Express Journals, 2022)
Intrauterine infection of the fetus is an antenatal risk, the absence of clear clinical signs makes it impossible to diagnose this perinatal pathology without modern clinical and laboratory diagnostic methods.
Keywords: Fetoplacental; intrauterine; fetus; cardiotocography